The development of stereocontrolled methods to obtain a diverse set of tetrahydroquinoline-based, natural product-inspired compounds - Esmaeelzadeh Khadem, Shahriar (University of Ottawa (Canada), 2010)
Over the years, it has been shown that natural products which are capable of acting as modulators (i.e., activators or inhibitors) of protein-protein interactions are highly complex and possess three-dimensional architectures with several chiral centers and a diverse range of protein-binding elements. These features appear to be required when it comes to dissecting protein functions with the help of small molecules. Therefore, it is not surprising that an interest in developing natural product-like small molecules, which could aid in understanding protein-protein interactions-based cellular signaling pathways, is growing. The success of the chemical genomics program that is aimed toward understanding complex protein networking and its roles in cellular signaling pathways depends on the availability of a diverse range of such chemical probes (Chapter 1). Tetrahydroquinoline-derived natural products have long been utilized as modulators of protein functions and belong to an important family of bioactive compounds. We had developed a practical enantioselective synthesis of tetrahydroquinolione-based functionalized scaffold (Chapter 2). The bicyclic scaffold is highly versatile and contains four orthogonally protected functional groups that could further be utilized in obtaining polycyclic compounds. In one case, we successfully developed a solution phase synthesis of the tricyclic derivative having a bridged 10 membered ring (Chapter 3). In the other case, tetrahydroquinoline-based polycyclics containing alpha,beta-unsaturated gamma-lactam and delta-lactone were synthesized (Chapter 4). The stereoselective ring closing metathesis was the key reaction in those syntheses. After the successful development of the methods in solution, some of the intramolecular and intermolecular stereoselective-based reactions had been tried on solid phase. Developing stereoselective reactions-based methods on solid phase is crucial for the rapid synthesis of analogs. Besides NMR, the conformation of the bridged 10 and 5-membered ring derivatives were assigned by X-ray studies (Chapter 3 and 4). In another study, a known polycyclic system containing tetrahydroquinoline was prepared using a tandem Povarov multi I component/cyclocondensation reaction. With our novel methodology, this complex system was constructed not only in one-pot, but also with high yield and complete stereo- and regio-selectivity (Chapter 5). Finally, one of the several possible applications for our synthesized compounds was investigated. The aim was seeking for the small molecules capable of modulation of the Bcl-2 family proteins (Chapter 6). The observed preliminary results were found to be promising as the starting point on the general goal of 'Finding Small-Molecule Perturbators of Protein-Protein Interactions as the Possible Drug Targets in Cancer Therapy'.
Keywords: Chemistry, Organic.